Clinical Evaluation of Specific Oral Manifestations in Pediatric Patients with Ascertained versus Potential Coeliac Disease: A Cross-Sectional Study. (13th August 2014) - Bramanti, Ennio; Cicciù, Marco; Matacena, Giada; Costa, Stefano; Magazzù, Giuseppe
Abstract : Patients involved on coeliac disease (CD) have atypical symptoms and often remain undiagnosed. Specific oral manifestations are effective risk indicators of CD and for this reason an early diagnosis with a consequent better prognosis can be performed by the dentist. There are not researches analysing the frequency of these oral manifestations in potential coeliac patients. The aim of this study is to investigate the oral hard and soft tissue lesions in potential and ascertained coeliac children in comparison with healthy controls. 50 ascertained children, 21 potential coeliac patients, and 54 controls were recruited and the oral examination was performed. The overall oral lesions were more frequently present in CD patients than in controls. The prevalence of oral soft tissue lesions was 62% in ascertained coeliac, 76.2% in potential coeliac patients, and 12.96% in controls (P < 0.05 ). Clinical dental delayed eruption was observed in 38% of the ascertained coeliac and 42.5% of the potential coeliac versus 11.11% of the controls (P < 0.05 ). The prevalence of specific enamel defects (SED) was 48% in ascertained coeliac and 19% in potential coeliac versus 0% in controls (P < 0.05 ; OR = 3.923 ). The SED seem to be genetically related to the histological damage and villous atrophy.